Utilization of Information and Communication Technology in Optimizing the Quality of Public Relations at Schools Based on Pesantren - Buyamin Buyamin (Journal of Research in Educational Management, 2022)
The purpose of this study was to find out the efforts to use information and communication technology  in optimizing the quality of public relations at Schools Based on Pesantren. This study uses qualitative methods to understand the use of information and communication technology  in public relations at Schools Based on Pesantren. Data were obtained through in-depth interviews and participatory observation with students, teachers, madrasa staff, parents and local residents. Data analysis was carried out thematically to explore meanings and interpretations related to the use of information and communication technology  in improving the quality of public relations in the madrasa. The results of this work are a) Utilization of information and communication technology  at Schools Based on Pesantren aims to improve the quality of education and community relations through adequate technological facilities and two-way communication with the community, with proper support and training. Thus, madrasas create a modern and inclusive learning environment and build harmonious community relations. b) Utilization of information and communication technology  at Schools Based on Pesantren aims to improve the quality of community relations through two-way communication and easy access to information, with infrastructure challenges and human resource readiness that need to be overcome to create an inclusive and participatory environment.